Diminutions of acceleration and deceleration output during professional football match play - Akenhead, R.; Hayes, P. R.; Thompson, K. G.; French, D. (Journal of Science and Medicine in Sport, 2013)
Objectives: This study examined distances covered at low (1-2 m s-2), moderate (2-3 m s-2) and high (>3 m s-2) acceleration (LACC, MACC and HACC respectively) and deceleration (LDEC, MDEC, and HDEC respectively) during competitive football games. Temporal and transient patterns of acceleration and deceleration were also examined. Design: Observational, repeated measures. Methods: Thirty-six professional male professional footballers were monitored using a 10 Hz non-differential global positioning system (NdGPS). Match data was organised into six 15 min periods (P1: 1-15 min, P2: 16-30 min, P3: 31-45 min, P4: 46-60 min, P5: 61-75 min, and P6: 76-90 min) for analysis of temporal patterns, and into eighteen 5 min periods for analysis of transient patterns. ANOVA with Bonferroni post hoc tests were used to identify significant (p < 0.05) differences between periods. Results: Distance covered at LACC, MACC, HACC, LDEC, MDEC, and HDEC was 424 ± 75 m, 242 ± 25 m, 178 ± 38 m, 365 ± 54 m, 210 ± 23 m and 162 ± 29 m respectively. Between period decrements ranged from 8.0% to 13.2% from P1 to P3, 9.2% to 16.3% from P4 to P6, and from 14.9% to 21.0% from P1 to P6. Following PEAK HACC (148% of mean 5 min HACC), HACC at 5POST was 10.4% lower than mean (p < 0.01). Conclusions: Time-dependent reductions in distances covered suggest that acceleration and deceleration capability are acutely compromised during match play. Further, the occurrence of transient fatigue may be supported by the findings that HACC and HDEC performance following PEAK was approximately 10% lower than mean values.